Malhas em Imagem: um projeto sobre a ourivesaria de Gondomar - Manuela Restivo (Midas: Museus e Estudos Interdisciplinares)
This article presents Malhas em Imagem, a project developed by the cultural association Casa do Vinhal that aims to promote the jewelry produced in Gondomar, namely the threads. The project goal is to highlight the variety of thread models, and the formal and technical complexity they may show, through an online repository with the different kinds of threads and information associated with each one. This text draws a brief state of the art about the research and work done disseminating goldsmithery from the north of Portugal, particularly from Gondomar, in order to contextualize and demonstrate the reasons at the basis of the project.